2018
DOI: 10.1111/bcpt.12997
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 Variation Affects Myelosuppression, Progression‐free Survival and Overall Survival in Paclitaxel/Carboplatin‐treated Ovarian Cancer Patients

Abstract: The standard chemotherapy for ovarian cancer is paclitaxel/carboplatin. Patients often exhibit myelosuppressive toxicity, and the treatment response varies considerably. In this study, we investigated the previously reported SNPs 1199G>A (rs2229109), 1236C>T (rs1128503), 2677G>T/A (rs2032582), 3435C>T (rs1045642) in ABCB1, and 1196A>G (rs10509681) in CYP2C8 and their association with treatment-induced myelosuppression, progression-free survival (PFS) and overall survival (OS). From the phase III study, OAS-07O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…Our study demonstrated the predictive value of ABCB1 C1236T for the PFS and OS in patients who were administered taxane-contained chemotherapy, which is consistent with the results reported by Bjorn et al [1] and Zhou et al [44]. The effect of genetic variation on prognosis may be related to mutations that cause changes in the encoded amino acids, affecting the normal function of certain drug transporters, such as decreased expression of P-gp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study demonstrated the predictive value of ABCB1 C1236T for the PFS and OS in patients who were administered taxane-contained chemotherapy, which is consistent with the results reported by Bjorn et al [1] and Zhou et al [44]. The effect of genetic variation on prognosis may be related to mutations that cause changes in the encoded amino acids, affecting the normal function of certain drug transporters, such as decreased expression of P-gp.…”
Section: Discussionsupporting
confidence: 91%
“…Significant heterogeneities were found in the overall meta-analysis of the homozygote model (I 2 = 56%, P = 0.03) and dominant model (I 2 = 53%, P = 0.03). Sensitivity analyses showed that heterogeneity was decreased in the heterozygous model (I 2 = 30%, P = 0.21) after excluding the study by Li et al and in the dominant model (I 2 = 7%, P = 0.0.37) after excluding the study by Bjorn et al (Arm A) [1].…”
Section: Osmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, numerous studies have shown that ABCB1 is widely expressed in human tumor cells at different stages 22 . The patients who suffer from tumors with high levels of ABCB1, including patients with colorectal cancer 23 , pancreatic cancer 24 , liver cancer 25 , adrenal cortex carcinoma 26 , acute leukemia 27 , and ovarian cancer 28 , are usually found to also have a poorer prognosis. It is also reported that ABCB1 has an important effect on absorption, distribution, metabolism, and excretion of its substrate drugs 29 .…”
Section: Discussionmentioning
confidence: 99%
“…18,25,26 Similar to studies of GST polymorphisms, the associations of ABCB1 genetic variation with treatment outcomes is inconsistent across studies. 27,28 Patients developing severe toxicities often require dose reduction, dose delay, or treatment interruption that require clinical interventions and may affect the disease prognosis. 4 However, no study has been found so far focus on regarding the utility of polymorphisms in the management of chemotherapy and toxicities for ovarian cancer.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%